Penerapan Digitalisasi Koperasi dan Pemasaran serta Pendampingan untuk Peningkatan Value Produk UMKM Anggota Koperasi LKMS Kasuwari di Pekalongan Barat - Naufal, Abdul Razak; Ngizudin, Risal; Rachdantia, Dheasari (Universitas Nusantara PGRI Kediri, 2025)
Technological advances have had a positive impact on various sectors, including cooperatives which are transforming towards digital services. Cooperatives, as business entities owned and operated by their members for the common good, have big challenges after the COVID-19 pandemic, especially in improving the economy through microfinance institutions. Many low-income people in developing countries, such as Indonesia, do not have access to credit or bank accounts, making it difficult to determine their creditworthiness. Microfinance Institution (LKMS) Kasuwari focuses on empowering productive women through financing and entrepreneurship training. This initiative not only helps small businesses, but also strengthens the local, family-based economy. Utilizing cooperative digitalization through marketplace applications, core banking systems and mobile banking systems can provide real solutions facing the LKMS Kasuwari cooperative.